Lexical Cohesion Used in “National Column” of the Jakarta Post - Sumani, Sumani; Kartikasari, Dyah (English Department, Universitas Negeri Surabaya, 2022)
A newspaper has three main functions: informing, serving, and entertaining. From a linguistic point of view, especially discourse analysis, it is interesting to analyze how the news can relate to each other and how the news has unity from one element to another. The instrument to relate and unite from one element to another in discourse analysis is called cohesion. Cohesion is a meaningful relationship between two or more elements within the text. Meanwhile, there are two kinds of cohesion, they are grammatical cohesion and lexical cohesion. In this study, the researcher focuses on lexical cohesion. Lexical cohesion is a linguistic device that helps create unity in the text. It occurs when two or more elements in the text are related to their meaning. Besides, it is also viewed as one of the elements that help the reader quickly understand the writer's thoughts. This study mainly analyzes lexical cohesion's types and functions in the